Fifty years of reduction in sulphur deposition drives recovery in soil pH and plant communities. (24th November 2022) - Seaton, Fiona M.; Robinson, David A.; Monteith, Don; Lebron, Inma; Bürkner, Paul; Tomlinson, Sam; Emmett, Bridget A.; Smart, Simon M.
Abstract: Sulphur deposition through rainfall has led to species loss and ecosystem degradation globally, and across Europe huge reductions in sulphur emissions since the 1970s were expected to promote the recovery of acidified ecosystems. However, the rate and ecological impact of recovery from acidification in terrestrial ecosystems is still unclear as is the influence of management and climate, as to date there has been no long‐term spatially extensive evaluation of these changes. Here, we present data from thousands of sites across Great Britain (pH range 3.3–8.7) surveyed repeatedly from 1978–2019 and assess change in soil pH and plant acidity preference (Ellenberg R) in response to atmospheric deposition of sulphur and nitrogen. We analyse change in grasslands managed for pasture, referred to as high‐intensity habitats, and compare to seminatural habitats comprising rough grassland, broadleaved woodland, bog and heathland, referred to as low‐intensity habitats. Soil pH increased from 1978 to 2007 but then decreased between 2007 and 2019, resulting in a net increase of 0.2 pH units in low‐intensity habitats but no change in high‐intensity habitats. The community average Ellenberg R increased in seminatural habitats by 0.2 units but remained stable in intensive grasslands. In seminatural habitats, but not intensive grasslands, these changes in plant community composition were associated with the soil pH changes which were in turn linked to decreasing sulphur deposition and differences in rainfall. Nitrogen deposition, which was relatively stable over the survey period, showed no additional effect upon soil acidity once sulphur deposition was accounted for. Synthesis : Our results provide conclusive evidence that reductions in acid emissions are stimulating the gradual recovery of chronically acidified terrestrial ecosystems at a whole‐country scale, while also suggesting this recovery is being compromised by changing climate and land management. Abstract : This study assesses changes in soil pH and the plant community across Great Britain from 1978–2019. Soil pH has increased then decreased over these four decades, and vegetation in seminatural habitats has showed continued recovery from acidification. This ecosystem recovery is associated with reductions in acid deposition, however is being affected by changing climate and land management.